2017
DOI: 10.4236/as.2017.810080
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Anthracnose Disease Resistance on Chili Fruit by Treatment of Oligochitosan—Nanosilica Hybrid Material

Abstract: Oligochitosan (OC) with molecular weight Mw of 5000 g/mol was prepared by gamma Co-60 ray irradiation of chitosan solution. Nanosilica (nSiO 2 ) with the size of 10 -30 nm was synthesized by calcination of acid treated rice husk. The mixture of 1% OC -1% nSiO 2 was prepared by dispersion of nSiO 2 in OC solution. The morphology of nSiO 2 in the mixture of OC-nSiO 2 was measured from images of transmission electron microscopy (TEM). The effect of foliar application of the mixture of OC-nSiO 2 on the induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The present study showed a reduction in dry weight and RGR under drought stress where COS treatment did not significantly improve growth parameters. Without stress, chitosan (Ait Barka et al, 2004;Mondal et al, 2016;Harfoush et al, 2017) and degraded chitosan (such as COS) have been reported to improve growth in different species (Dzung et al, 2011;Rahman et al, 2013;Dzung et al, 2017;Muley et al, 2019). However, in A. annua plants under well-irrigated conditions, differences between treatments were not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present study showed a reduction in dry weight and RGR under drought stress where COS treatment did not significantly improve growth parameters. Without stress, chitosan (Ait Barka et al, 2004;Mondal et al, 2016;Harfoush et al, 2017) and degraded chitosan (such as COS) have been reported to improve growth in different species (Dzung et al, 2011;Rahman et al, 2013;Dzung et al, 2017;Muley et al, 2019). However, in A. annua plants under well-irrigated conditions, differences between treatments were not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…Jaleel et al (2017) also found an enhancement in biomass parameters and an increased yield of essential oil and citral content in lemongrass (Cymbopogon flexuosus (Steud.) Wats) treated with COS. Foliar spray with COS improved shoot fresh weight, shoot dry weight and fruit fresh weight of chili (Capsicum frutescens L.) plants (Dzung et al, 2017). Promising results were also obtained with COS-treated wheat seedlings, where growth parameters improved (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Afterward, the topsoil is covered with a damp cloth, and the plants are covered with transparent plastic for 2 days. After 2 days, the cover is removed, and the plants are placed in a shaded area (Dzung et al, 2017;Srisapoom et al, 2021).…”
Section: Testing Chili Resistance Levelsmentioning
confidence: 99%
“…Yet another technique could be application of biological substances in the form of nanoparticles. In this direction, oligochitosan from shrimp shells irradiated with Co-60 combined with nano-silicon (10-30 nm), sprayed three times before fruiting as 60 mg L -1 each found effective in controlling the anthracnose infection to the tune of only 22.2 % as against the control with 90 % anthracnose infection (Dzung et al, 2017). Another approach could be the acquired resistance, which is eco-friendly concept through host plant derived signal molecules.…”
Section: Use Of Other Biologicalcompoundsmentioning
confidence: 99%